2021
DOI: 10.1002/cam4.3914
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐reported distress and age‐related stress biomarkers among colorectal cancer patients

Abstract: Objective Distress among cancer patients has been broadly accepted as an important indicator of well‐being but has not been well studied. We investigated patient characteristics associated with high distress levels as well as correlations among measures of patient‐reported distress and “objective” stress‐related biomarkers among colorectal cancer patients. Methods In total, 238 patients with colon or rectal cancer completed surveys including the Distress Thermometer, Problem List, and the Hospital Anxiety and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…symptoms, than did older patients (Goulia et al, 2012). This may be because younger patients are more likely to describe their psychological distress and need more help than older patients (Eddington et al, 2021). Another possible explanation for this discrepancy is that older patients make better use of suppression, an emotion regulation strategy, than younger patients when encountering psychological distress (Muazzam et al, 2021).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…symptoms, than did older patients (Goulia et al, 2012). This may be because younger patients are more likely to describe their psychological distress and need more help than older patients (Eddington et al, 2021). Another possible explanation for this discrepancy is that older patients make better use of suppression, an emotion regulation strategy, than younger patients when encountering psychological distress (Muazzam et al, 2021).…”
Section: Discussionmentioning
confidence: 98%
“…Goulia et al even demonstrated that in a cohort of patients with severe chronic medical illnesses, a larger proportion of younger patients (<65 years) had severe psychological distress, predominantly depression, anxiety, and hostility symptoms, than did older patients (Goulia et al, 2012). This may be because younger patients are more likely to describe their psychological distress and need more help than older patients (Eddington et al, 2021). Another possible explanation for this discrepancy is that older patients make better use of suppression, an emotion regulation strategy, than younger patients when encountering psychological distress (Muazzam et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of thyroid cancer remains 3 times higher in women who are more likely to be diagnosed with small PTCs. 4 Despite these differences, limited investigation exists into how sex and gender influence thyroid cancer-related information processing and decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Concerns expressed by patients with newly diagnosed low-risk papillary thyroid cancer (PTC) relate to the cancer and its associated future outcome uncertainty as well as the potential risks and consequences of its treatment (eg, thyroidectomy). 4 It is important to fully understand the fears experienced by individuals newly diagnosed with thyroid cancer to inform supportive care strategies and patient counseling. This understanding may be more fully informed in considering the context of gender.…”
mentioning
confidence: 99%
“…28 It has been observed that the activity of this axis tends to decrease in the elderly, probably due to the reduction in sleep hours, causing the appearance of various neurodegenerative disorders. 30 Another fundamental structure of the HPA axis is the amygdala, related to emotional processing, specifically to the regulation of fear. Chronic stress causes constant exposure to corticotropinreleasing hormone (CRH), altering the volume and functions of the amygdala.…”
Section: Hpa Axis Activitymentioning
confidence: 99%